PENGARUH KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUASAN PELANGGAN PADA PT MATAHARI DEPARTMENT STORE - Sari, Desi Indah; Raymond, Raymond (SCIENTIA JOURNAL, 2019)
Matahari Department Store is a retail company in Indonesia which is the owner of a department store chain. The Sun became one of the most famous shopping malls in Indonesia provides convenience for the public to shop all needs. this research aims to know the influence of product quality and customer satisfaction towards the promotion of PT Matahari Department Store Keprimall. The samples on this research as much as 100 respondents using the technique of sampling accidental sampling. As for the variables used the quality of the products (X 1), promotion (X 2) as free and customer satisfaction variable (Y) as a variable. Technique of data analysis in this study uses multiple linear regression method. The results of this study showed that the quality of the products, the promotion of a positive effect towards customer satisfaction in PT Matahari Department Store.